Jerky dystonic tremor: a less-recognized feature of DYT-THAP1 - Narendrakumar H Barad (Annals of Movement Disorders, 2021)
Dystonia is a very complex movement disorder. Recently, the classification of dystonia has been updated by a group of experts to simplify the clinical approach to dystonia. As per this new classification, clinically we can divide dystonia into either isolated or combined dystonia. In the isolated group, dystonia is the only feature with or without tremor. In the isolated dystonia (DYT) group, DYT-TOR1A and DYT-THAP1 are the commoner entities worldwide. In DYT-THAP1 cases, apart from classic generalized dystonia phenotype, appendicular tremor has also been described. However, in some cases, it could be jerky and may create confusion with myoclonus. To prevent this confusion and subsequent investigations in the line of myoclonic dystonic syndromes, identification of this jerky tremor assumes great clinical significance. Hereby, we are describing a genetically confirmed DYT-THAP1 patient with a jerky dystonic tremor of upper limbs.